PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, SANKSI PERPAJAKAN, KESADARAN WAJIB PAJAK, PENGETAHUAN DAN PEMAHAMAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK (Studi Empiris Pada Wajib Pajak UMKM yang Terdaftar di KPP Pratama Dumai) - Putri Elisa; Zirman Zirman; Wahyuni Nita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of the modernization of the taxadministration system, taxation sanctions, awareness of taxpayers, knowledge andunderstanding of taxpayers on the level of UMKM taxpayer compliance at KPP PratamaDumai. The population in the study were micro, small and medium enterprises (UMKM)taxpayers registered at the Pratama Dumai Tax Service Office (KPP), which numberedcurrently around 8,431 registered taxpayers and some 4,245 registered taxpayers paidtaxes. Sampling is done by accidental sampling method which is as many as 99 taxpayersof micro, small and medium enterprises. The type of data used is primary data using thequestionnaire method. The data analysis method used in this study is MultipleRegression. With the help of SPSS version 24 software. The results of hypothesis testingusing t statistical tests show the significance value of the tax administration systemmodernization variable 0.928> 0.05 which means H1 is rejected, tax sanctioned variable0.018 <0.05 which means H2 is accepted, taxpayer awareness variable 0.855> 0.05which means H3 is rejected, variable knowledge and understanding of taxpayer 0.536>0.05, which means that H4 is rejected. The results showed that the variables ofmodernization of the tax administration system, taxation sanctions, awareness oftaxpayers, knowledge and understanding of taxpayers did not affect simultaneously andsignificantly on the level of UMKM taxpayer compliance at KPP Pratama Dumai.Keywords : Modernization of Taxation Administration System, Taxation Sanctions,Taxpayer Awareness,Taxpayer Knowledge and Understanding, TaxpayerCompliance Level